Description of thyroid disorders the year before conception: a population-based study - Tena Vivó, Glòria; Parellada Esquius, Neus; Cunillera Puértolas, Oriol; Albareda Riera, Mercè; Isidro Albaladejo, Mónica; Vila Ballester, Lluís (Frontiers in Endocrinology, 2023)
Objective: The aim of this study is to estimate the prevalence of previously identified thyroid disorders and hypothyroidism monitoring before pregnancy. Material and Methods: A retrospective cross-sectional study of women whose pregnancies occurred between 2014-2016 was conducted, including 120,763 pregnancies in Catalonia (Spain). The presence of thyroid disorders in women was based on the disease diagnostic codes and/or the prescription of levothyroxine or antithyroid drugs. In order to evaluate the thyroid disorders diagnosis and monitoring Thyrotropin (TSH), free T4 (FT4), antiperoxidase antibodies (TPOAb) and the anti-TSH receptor antibodies (TRAb) records were gathered and categorized according to the reference values of each laboratory. Results: The prevalence of recorded thyroid disorders prior to last menstrual period date was 5.09% for hypothyroidism and 0.64% for hyperthyroidism, both prevalences (hypothyroidism and hyperthyroidism) showing a significant increase with age. A thyroid-monitoring test was not performed in the year before to last menstrual period date in approximately 40% of the women with a known thyroid disorder. Among the women with hypothyroidism who had a TSH test recorded, 31.75% showed an above-normal result. Among women previously unknown to have thyroid disorders, 3.12% of them had elevated TSH and 0.73% had low TSH. Conclusion: A high percentage of Catalan women with a known thyroid disorder were not properly monitored during the year before pregnancy. Among those who were monitored, more than a third had TSH values out of the reference range. Therefore, it would be important to evaluate women with thyroid disorders in a pre-pregnancy visit.